THE RELATIONSHIP AMONG MANAGERIAL CAPABILITY, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND EMPLOYEE PERFORMANCE: MEDIATION EFFECTS OF ORGANIZATIONAL CULTURE - Suharto, Suharto; Nusantoro, Jawoto (Universitas Negeri Medan, 2018)
AbstractThis study aims to determine the direct effects of managerial skills, organizational citizenship behavior and organizational culture on employee performance. The method used bothered survey method as well as primary data. The fluctuating productivity of MSME is largely due to the relatively high various performance of the employee, and it can disrupt the stability of small businesses as the starting point of this research. The sampling namely with used bothered forcible entry sampling. Chaired by the manifest variables used Likert scale installation design to 160 talk shows us the respondents at MSME in Lampung Province. Testing requirements analysis included lilliefors test normality, homogeneity test, linearity test and regression yew. The data bothered analyzed using structural equation model, namely structural equation modeling. The research results find that managerial ability provides direct effects on organizational culture, organizational citizenship behavior provides direct effects on organizational culture, managerial ability does not provide direct effects on employee performance, organizational citizenship behavior provides direct effects on employee performance and organizational culture provides direct effects on employee performance.Keywords: Managerial Capability, Organizational Citizenship Behavior, Organizational Culture, Employee Performance.